THE MAINTENANCE OF JAVANESE LANGUAGE BY MINORITY LIVING IN KECAMATAN ANJUNGAN PONTIANAK - Amrina Sari, Riski (Jurnal Ilmiah Spectral, 2018)
This research explained the language maintenance of Javanese in Kecamatan Anjungan Pontianak. The purposes of this research are to find out the factors affecting language maintenance of Javanese language in Kecamatan Anjungan. The method of this study was descriptive qualitative research. The participants were 20 Javanese people who live in Kecamatan Anjungan Pontianak taken by purposive random sampling. The data were taken through interview and observation. This researcher found the following results, there are five factors affecting Javanese language maintenance by minority living in Kecamatan Anjungan such as: Socio-Demographic, Endogamy (intramarriage), Family domain, neigborhood domain, ethno linguistic vitality.